2015
DOI: 10.1094/pdis-04-14-0341-re
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization ofDidymella bryoniaeIsolates Infecting Watermelon and Other Cucurbits in Florida and Georgia

Abstract: Gummy stem blight caused by Didymella bryoniae (anamorph Phoma cucurbitacearum) is a major fungal disease of watermelon (Citrullus lanatus) and other cucurbits. Thirty-five isolates of Didymella and Phoma spp. associated with symptoms of gummy stem blight on watermelon, Canary melon (Cucumis melo), muskmelon (C. melo), and winter squash (Cucurbita maxima) from Florida and Georgia were characterized based on morphology on agar media, pathogenicity on ‘Melody’ watermelon, the internal transcribed spacer (ITS) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Results confirmed that the fungal isolate was sharing 99% homology with the S. cucurbitacearum isolate (NCBI accession no.KC460840.1) available in the database submitted by Liu et al (2013). Isolated DNA was also used to amplify with SCAR primers (RG-I-F 5'-TGTCGTTGACATCATTCCAGC-3′ and RG-I-R 5'-ACCACTCTGCTTAGTATCTGC-3′) which are specific to S. cucurbitacearum (Babu et al 2015). The amplicon obtained with this primer was of 735 bp size.…”
mentioning
confidence: 99%
“…Results confirmed that the fungal isolate was sharing 99% homology with the S. cucurbitacearum isolate (NCBI accession no.KC460840.1) available in the database submitted by Liu et al (2013). Isolated DNA was also used to amplify with SCAR primers (RG-I-F 5'-TGTCGTTGACATCATTCCAGC-3′ and RG-I-R 5'-ACCACTCTGCTTAGTATCTGC-3′) which are specific to S. cucurbitacearum (Babu et al 2015). The amplicon obtained with this primer was of 735 bp size.…”
mentioning
confidence: 99%
“…Assignment to the RGI and RGII genotypes of D. bryoniae strains in this study was performed by an RG-specific PCR according to previously published protocols ( Keinath et al, 2001 ; Somai et al, 2002 ; Babu et al, 2015 ). In brief, PCRs were performed in a 25 μL reaction mixture containing 40 ng DNA, 2.0 μL 10x reaction buffer [50 mM Tris/HCl (pH 8.8), 1.5 mM MgCl 2 , 15 mM (NH 4 ) 2 SO 4 and 0.1% Triton X-100], 200 μM dNTPs, 2.5 U Taq DNA polymerase (5 U μL -1 ), and 0.25 μM each primer.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, PCRs were performed in a 25 μL reaction mixture containing 40 ng DNA, 2.0 μL 10x reaction buffer [50 mM Tris/HCl (pH 8.8), 1.5 mM MgCl 2 , 15 mM (NH 4 ) 2 SO 4 and 0.1% Triton X-100], 200 μM dNTPs, 2.5 U Taq DNA polymerase (5 U μL -1 ), and 0.25 μM each primer. The thermal cycling program was: 94°C for 2 min, and 35 cycles of 94°C for 1 min, 62°C for 1 min, and 72°C for 2 min ( Babu et al, 2015 ). The DB17 primer set was used to amplify the conserved SCAR common to both genotypes of D. bryoniae ( Table 2 ) ( Ling et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Asia occupied more than 80% watermelon production all over the world. However, while anthracnose (Zhou & Everts, 2012), gummy stem blight (Babu et al, 2015) and powdery mildew (Keinath & DuBose, 2004) impacted on watermelon production for a long time, some pesticides should be applied to control the fungal threat. As two kinds of broad-spectrum fungicides, strobilurin fungicides and demethylation inhibiting fungicides were effective to above fungal threats (Gopinath, Radhakrishnan, & Jayaraj, 2006;Reuveni, 2000;Thomas, Langston, Sanders, & Stevensosn, 2012) on many fruits and vegetables, e.g.…”
Section: Introductionmentioning
confidence: 99%